2010
DOI: 10.1017/s095026881000066x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination and social inequality: results from a prospective cohort study

Abstract: We investigated the effect of social inequalities on the uptake of human papillomavirus (HPV) vaccination, combining data from a feasibility study conducted in 2007-2008 in 2817 secondary schoolgirls in two UK primary-care trusts, with census and child health records. Uptake was significantly lower in more deprived areas (P<0·001) and in ethnic minority girls (P=0·013). The relatively small proportion of parents who actively refused vaccination by returning a negative consent form were more likely to come from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 19 publications
3
47
0
Order By: Relevance
“…However, in one study (Dempsey et al, 2010) Black and Caucasian girls were more likely to initiate the vaccination program than other girls, and in a second study Hispanic girls were significantly more likely to refuse the HPV vaccination than Caucasian girls. In contrast, several studies showed no significant differences in rates of vaccine initiation based on ethnicity or race (Allen et al, 2010;Pruitt and Schootman, 2010;Reiter et al, 2010;Roberts et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…However, in one study (Dempsey et al, 2010) Black and Caucasian girls were more likely to initiate the vaccination program than other girls, and in a second study Hispanic girls were significantly more likely to refuse the HPV vaccination than Caucasian girls. In contrast, several studies showed no significant differences in rates of vaccine initiation based on ethnicity or race (Allen et al, 2010;Pruitt and Schootman, 2010;Reiter et al, 2010;Roberts et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In a study investigating the effect of social inequalities on the uptake of HPV vaccine in the UK, the authors found that HPV vaccine uptake was significantly lower in more deprived areas and in ethnic minority girls. 21 It will be important in future studies in Germany to record ethnicity on vaccine uptake monitoring activities to complete the panel of possible predictors for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of mainly North American studies has reported that young Black women are less likely to initiate HPV vaccination compared to young White women 37. In a pilot study carried out before the introduction of the HPV vaccine in the UK, uptake was lower in schools with greater ethnic diversity,38 39 and analyses of data from the first year of the vaccination programme (routine and ‘catch-up’ cohorts) also suggest that ethnicity is an important factor in understanding uptake in the UK 35. Research from the UK has also suggested that there is lower awareness and acceptability of the HPV vaccine among ethnic minority groups 40.…”
Section: Discussionmentioning
confidence: 99%